Gestational Hypothyroxinemia Affects Its Offspring With a Reduced Suppressive Capacity Impairing the Outcome of the Experimental Autoimmune Encephalomyelitis - Haensgen, Henny; Albornoz, Eduardo; Opazo, María C.; Bugueño, Katherinne; Jara Fernández, Evelyn Liliana; Binzberger, Rebecca; Rivero-Castillo, Tomás; Venegas Salas, Luis F.; Simon, Felipe; Cabello-Verrugio, Claudio; Elorza, Alvaro A.; Kalergis, Alexis M.; et al. (Frontiers in Immunology, 2018)
Hypothyroxinemia (Hpx) is a thyroid hormone deficiency (THD) condition highly frequent during pregnancy, which although asymptomatic for the mother, it can impair the cognitive function of the offspring. Previous studies have shown that maternal hypothyroidism increases the severity of experimental autoimmune encephalomyelitis (EAE), an autoimmune disease model for multiple sclerosis (MS). Here, we analyzed the immune response after EAE induction in the adult offspring gestated in Hpx. Mice gestated in Hpx showed an early appearance of EAE symptoms and the increase of all parameters of the disease such as: the pathological score, spinal cord demyelination and immune cell infiltration in comparison to the adult offspring gestated in euthyroidism. Isolated CD4+CD25+ T cells from spleen of the offspring gestated in Hpx that suffer EAE showed reduced capacity to suppress proliferation of effector T cells (TEff) after being stimulated with anti-CD3 and anti-CD28 antibodies. Moreover, adoptive transfer experiments of CD4+CD25+ T cells from the offspring gestated in Hpx suffering EAE to mice that were induced with EAE showed that the receptor mice suffer more intense EAE pathological score. Even though, no significant differences were detected in the frequency of Treg cells and IL-10 content in the blood, spleen and brain between mice gestated in Hpx or euthyroidism, T cells CD4+CD25+ from spleen have reduced capacity to differentiate in vitro to Treg and to produce IL-10. Thus, our data support the notion that maternal Hpx can imprints the immune response of the offspring suffering EAE probably due to a reduced capacity to trigger suppression. Such “imprints” on the immune system could contribute to explaining as to why adult offspring gestated in Hpx suffer earlier and more intense EAE.